Rancang Bangun Sistem Otomatisasi Rumah Berbasis Internet of Thing Dengan Telegram - Yohanes Prasetiya; Rino (Komunitas Dosen Indonesia, 2022)
The purpose of this research is to design an application to automate electronic devices so that they can turn on and off automatically and to create a home security application with access and proximity sensors in the form of RFID. The method used in this study is a home automation system based on the internet of things with telegram. The results in this study are that using an internet of things-based home automation system can improve home security with entry access. By using a home automation system based on the internet of things, it can make it easier to control home electronics through applications and the results of the answers to the questionnaire respondents are above 50% on average in choosing the answer